6. Q6e
Save videos to My Cheatsheet for later, for easy studying.
Video Solution
Q1
Q2
Q3
L1
L2
L3
Similar Question 1
<p>Simplify. Express answers in rational form with positive exponents.</p><p><code class='latex inline'> \displaystyle \left( \frac{(x^{18})^{\frac{-1}{6}}}{\sqrt[5]{243x^{10}}} \right)^{0.5} </code></p>
Similar Question 2
<p>Simplify. Express answers with positive exponents.</p><p><code class='latex inline'> \displaystyle \left( \frac{(32x^{5})^{-2}}{(x^{-1})^{10}} \right)^{0.2} </code></p>
Similar Question 3
<p>Simplify. Express answers with positive exponents.</p><p><code class='latex inline'> \displaystyle \left( \frac{(32x^{5})^{-2}}{(x^{-1})^{10}} \right)^{0.2} </code></p>
Similar Questions
Learning Path
L1 Quick Intro to Factoring Trinomial with Leading a
L2 Introduction to Factoring ax^2+bx+c
L3 Factoring ax^2+bx+c, ex1
Now You Try
<p>Evaluate each expression. Express answers in rational form with positive exponents.</p><p><code class='latex inline'>\displaystyle \frac{(81x^{4}y^{6})^{\frac{1}{2}}}{8(x^{9}y^{3})^{\frac{1}{3}}}</code> for <code class='latex inline'>x = 10, y = 5</code> </p>
<p>If <code class='latex inline'>\displaystyle M = \frac{(16x^{8}y^{-4})^\frac{1}{4}}{32x^{-2}y^{8}}</code>, determine values for <code class='latex inline'>x</code> and <code class='latex inline'>y</code> so that M = 1</p>
<p>Convert the following into exponents with rational powers and simplify using laws of exponents.</p><p><code class='latex inline'>\displaystyle (2x^4y^{-\frac{4}{5}})^3(8y^2)^{\frac{2}{3}} </code></p>
<p>Simplify <code class='latex inline'>\displaystyle \frac{ \sqrt{x(x^{2n+1})} }{ \sqrt[3]{x^{3n}} }</code>, <code class='latex inline'>x > 0</code>.</p>
<p>Simplify. Express answers in rational form with positive exponents.</p><p><code class='latex inline'> \displaystyle \left( \frac{\sqrt{64a^{12}}}{(a^{1.5})^{-6}} \right)^{\frac{2}{3}} </code></p>
<p>Evaluate each expression. Express answers in rational form with positive exponents.</p><p><code class='latex inline'>\displaystyle \left( \frac{(25a^{4})^{-1}}{(7a^{-2}b)^2} \right)^{\frac{1}{2}}</code> for <code class='latex inline'>a = 11, b = 10</code></p>
<p>Evaluate each expression. Express answers in rational form with positive exponents.</p><p><code class='latex inline'>\displaystyle \left( \frac{(4x^3)^4}{(x^{3})^{6}} \right)^{-0.5}</code> for <code class='latex inline'>x = 5</code></p>
<p>Convert the following into exponents with rational powers and simplify using laws of exponents.</p><p><code class='latex inline'>\displaystyle \frac{(9st)^{\frac{3}{2}}}{(27s^3t^{-4})^{\frac{2}{3}}} </code></p>
<p>Simplify. Express answers in rational form with positive exponents.</p><p><code class='latex inline'> \displaystyle (36m^{4}n^{6})^{0.5}(81m^{12}n^{8})^{0.25} </code></p>
<p>Evaluate each expression. Express answers in rational form with positive exponents.</p><p><code class='latex inline'>\displaystyle \frac{(9p^{-2})^{\frac{1}{2}}}{6p^2}</code> for <code class='latex inline'>p = 3</code></p>
<p>Evaluate each expression. Express answers in rational form with positive exponents.</p><p><code class='latex inline'>\displaystyle (16x^{6}y^{4})^{\frac{1}{2}}</code> for <code class='latex inline'>x = 2, y = 1</code></p>
<p>Simplify. Express answers in rational form with positive exponents.</p><p><code class='latex inline'> \displaystyle \left( \frac{(x^{18})^{\frac{-1}{6}}}{\sqrt[5]{243x^{10}}} \right)^{0.5} </code></p>
<p>Simplify. Express answers with positive exponents.</p><p><code class='latex inline'> \displaystyle \left( \frac{(32x^{5})^{-2}}{(x^{-1})^{10}} \right)^{0.2} </code></p>
<p>Convert the following into exponents with rational powers and simplify using laws of exponents.</p><p><code class='latex inline'>\displaystyle \frac{1}{(\frac{\sqrt{2}x^{-2}}{\sqrt{16}})^2} </code></p>
<p>Simplify using the laws of exponents. Express your final answer with only positive powers and prime base.</p><p><code class='latex inline'>\displaystyle (-\frac{27}{8})^{\frac{2}{3}}\times (\frac{25}{64})^{-\frac{3}{2}} </code></p>
<p>Convert the following into exponents with rational powers and simplify using laws of exponents.</p><p><code class='latex inline'>\displaystyle (\sqrt[5]{x^2y})^{\frac{2}{5}} </code></p>
<p>Simplify. Express your answers using only positive exponents. </p><p><code class='latex inline'> \displaystyle (8x)^{\frac{2}{3}}(27x)^{-\frac{1}{3}} </code></p>
How did you do?
I failed
I think I failed
I think I got it
I got it
Another question?
Found an error or missing video? We'll update it within the hour! 👉
Report it
Save videos to My Cheatsheet for later, for easy studying.